Ontology-based web annotation framework for hyperlink structures - Naing, Myo Myo (2010)
Heterogeneous and autonomous web sites contain information that cannot be easily processed by automated tools. To address the heterogeneity issues, one attempt is to add metadata to Web pages to provide semantic description of